Les idéologies du territoire : des alibis pour les politiques éducatives en milieu rural ? - Yves Alpe; Jean-Luc Fauguet (Nantes Université, 2010)
The educational policies are often based on a stigmatized vision of the rural space, designed like a space marked by the delay of development and the refusal of modernity. Thus a "territorial ideology" is built, which grows like an alibi: the reports/ratios of force and the social stakes disappear behind the territory. This design, largely diffused, ends up influencing the representations of the local actors: whereas the school performances of the rural pupils are of good level, their school trajectories testify to a "identity discredit", which influences their school and professional projects. On a plan plus general, the territorialized practices of the local actors remain rather largely unknown, whereas a better comprehension of the report/ratio to the territory could improve the effectiveness of the interventions of the public power, particularly in the field of education.